Diseño editorial como medio de difusión gastronómica del cantón Salcedo - Porras Lloacana, Kevin Santiago (2024)
This project aims to disseminate the gastronomic wealth of the different parishes of the Salcedo canton, addressing the notable lack of knowledge about the cultural identity of the canton that has emerged in recent years. It is crucial to analyze the reasons behind this decrease in knowledge, focusing on the characteristic dishes of each sector and proposing solutions based on graphic design to disseminate the information collected and revitalize interest in this topic. The project initiative was born from the need of citizens to have accesible and specific information about the gastronomy of each parish. Inresponse, the project focuses on gastronomic traditions, using graphic design as the main tool to communicate and spark interest in learning more about these traditions. The main objective of the project is not only to highlight the culinary traditions of the Salcedo canton, but also to propose effective solutions to disseminate this information. Through these efforts, Salcedo is sought to be recognized not only as a tourist destination, but also for its valuable gastronomic heritage.